Working conditions and self-management of diabetes mellitus type II: exploratory systematic review - Chávez Ramos, Wendy Janeth (Universidad de Sonora, 2022)
Introduction: The self-management of diabetes mellitus implies a set of activities that people have to perform in order to meet therapeutic, pharmacological, and dietary and personal hygiene measures recommended. There are factors of the labor environment that increases the risk to develop the illness; however, its relationship with self-management of those who already have the illness is not very clear yet. Objective: Explore available evidence about the subject of working conditions and self-management of diabetes mellitus type II. Methodology: Exploratory  systematic revision in databases such as PubMed, Scopus, Web of Science, Scielo, and Citation Index, eligibility criteria, quantitative and qualitative studies in human beings, opinions of experts and conference reports, using the concepts of diabetes mellitus type 2, working conditions and self-management. Preferred Reporting Items for Systematic reviews and Meta-Analyses were used; five phases of study were used, obtaining a final sample of six articles. Results: Of the articles, 1840 workers from 20 to 65 years of age were reported; from this amount 56% were male. The working conditions included shift and working hours, psychosocial stress, work load and control, social activities, non-scheduled work, illness self-report, satisfaction with work and type of occupation. For the self-management of the illness the metabolic control, glucose control, health status, diet, exercise, and essential practices in diabetes were included.  Conclusions: The absence of conceptual definitions, the difference between operational definitions and empiric indicators and the scares information available made difficult the comparison of results and the establishment of the relation between the study variables.